EFFECTS OF WATER DEFICIT ON MAZE SEEDLINGS GROWTH TRAITS - Shafique, F; Ali, Q; Malik, A (Biological and Clinical Sciences Research Journal, 2020)
Many biotic and abiotic factors affect plant growth and its development. Maize growth usually increased under excess water availability but less tolerant against water deficit stress condition. In this study, we investigated the effects of water stress on the growth and yield of maize. We found that severe water stress during the seedling stage had a greater effect on the growth and development of maize. Three maize varieties (Pak afghoi, Neelum, White corn) were used to find out the effects on growth of plant under drought or water deficit environmental conditions. Different drought stress treatments (Control, 20% irrigation water, 40% irrigation water, 60% irrigation water, 80% irrigation water) were imposed to growing seedlings after germination. The treatments were applied after 4 times each after 7 days interval and data for different morphological traits was recorded each time. The recorded data was pooled and analyzed for analysis of variance to access the significance of results. The ANOVA indicated the differences among five different genotypes and 5 different treatments for all parameters were significant. Tukey’s test indicated that maize genotype White corn was more tolerant while genotype Neelum was more sensitive for drought stress conditions therefore, white corn maize genotype may be helpful for the development of drought tolerance maize varieties and hybrids. Positive and significant correlation was found for shoot length with all other studied traits under drought stress conditions. Treatment control, 80% and 60% irrigation water was less adverse for maize growth while treatment 20% irrigation water highly affected all maize genotypes, therefore maize genotypes may be grow under treatment 60% irrigation water.